KERAGAMAN CACING TANAH PADA LAHAN DENGAN BERBAGAI MASUKAN BAHAN ORGANIK DI DAERAH LAMPUNG UTARA - Wibowo S (Fakultas Pertanian Universitas Palangka Raya, 2016)
A study has been done to know earthworms diversity on land with different resources of organicmatter in North Lampung area, Sumatera.The land were secondary forrest, alley cropping with organicmater resources from gamal (Gliricidia sepium), soga (Peltophorumdasyrrachis) and mixture of G.sepium and P. dasyrrachis andrest land (without other organic matter resources except from harvestresidues of yellow corn (Zea mays).It have found seven species totaly in the research land. On thesecondary forrest was found seven species perfect. Changing it to alley cropping was consequenceone species lost (Metapheretima carolinensis) and changing it to general agriculture without otherorganic matter resources except from plant harvest residues was consequence two spesies lost (M.carolinensis and Dichogaster crawi). Different resources of organic matter on land were madeinquire factor of earthworms diversity that lived in the soil.